Seeking the Civilizational Ghosts: Some Remarks on Chinese and Russian Approaches to International Law Through Civilizational Values - Amarasinghe Battagodage Punsara Aravinda (Journal of Legal Studies, 2020)
This article seeks to examine the rigor of civilizational values in modern international law as a crucial factor and how historically different civilizational values have inculcated different approaches to international law. While critiquing the civilizational rhetoric built by European nations in creating Eurocentric international law, this article brings how international law has been perceived by China and Russia following their historical complexities. Results emerge from this paper will demonstrate the different diversity in international law.